Teachers’ Self-Assessment of and Perceptions on Higher-Order Thinking Skills Practices for Teaching Writing - Swaran Singh, Charanjit Kaur; Tao, Hai; Masa Singh, Tarsame Singh; Tee, Tze Kiong; Ong, Eng Tek; Maniam, Mahendran; Gopal, Revathi; Ahmad Zaini, Fadzllah (2023)
Cultivation of students’ higher-order thinking ability has become the main agenda of the education curriculum. The transfer of knowledge pertaining to higher-order thinking by teachers to the students can prepare the latter with the necessary attributes for the 21st century. The present study is aimed at exploring Malaysian secondary ESL (English as a Second Language) school teachers’ self-assessment of, and perceptions on the higher-order thinking skills practices for teaching writing. Using a mixed-method research design, the validated 30-item five-point Likert scale questionnaire with an open-ended question was administered to a group of respondents consisting of 72 ESL teachers. The findings indicated that the overall mean score of ESL teachers’ self-assessment of using higher-order thinking skills practices for teaching writing was at a high level. Meanwhile, their perceptions on the integration of higher-order thinking skills in the teaching of writing include the concern of students’ low proficiency, difficulties in implementing HOTS in writing, poor participation by passive students, and teachers’ attitude towards using HOTs for teaching writing. This study suggests that fostering and creating awareness of mastering the elements of HOTS can benefit both the teachers and the students. Teachers have to be creative and innovative in their teaching so that the students can be given the opportunity to showcase their knowledge, skills and abilities in the quest to imbue them with the 21st century life skills.